NECTEC’s Participation in WAT-2021 - Zar Zar Hlaing; Ye Kyaw Thu; Thazin Myint Oo; Mya Ei San; Sasiporn Usanavasin; Ponrudee Netisopakul; Thepchai Supnithi (My University, 2021)
In this paper, we report the experimental results of Machine Translation models conducted by a NECTEC team (Team-ID: NECTEC) for the WAT-2021 Myanmar-English translation task Basically, our models are based on neural methods for both directions of English-Myanmar and Myanmar-English language pairs. Most of the existing Neural Machine Translation (NMT) models mainly focus on the conversion of sequential data and do not directly use syntactic information. However, we conduct multisource neural machine translation (NMT) models using the multilingual corpora such as string data corpus, tree data corpus, or POS-tagged data corpus. The multisource translation is an approach to exploit multiple inputs (e.g. in two different formats) to increase translation accuracy. The RNN-based encoder-decoder model with attention mechanism and transformer architectures have been carried out for our experiment. The experimental results showed that the proposed models of RNNbased architecture outperform the baseline model for the English-to-Myanmar translation task, and the multi-source and sharedmulti-source transformer models yield better translation results than the baseline.
Keywords: Natural Language Processing Techniques; Topic Modeling; Speech Recognition and Synthesis